Family Ownership and Corporate Performance - I Putu Sugiartha Sanjaya; Rayenda Khresna Brahmana; Wimpie Yustino Setiawan (ITB AAS INDONESIA, 2022)
The paper aims to investigate whether family ownership as controlling shareholder effect on firm performance. This paper uses ultimate (direct and indirect) ownership to identify a listed firm owned by family or non-family. Family ownership is majority shareholder for listed companies in Indonesia. Family ownership will be good impact (competitive advantage) or bad impact (private benefit) on companies. The study also motivates to study this topic because investigating on family ownership as controlling shareholder is limited in Indonesia. The study uses panel data or pooled data. The method for collecting data is archival. Unit of analysis of the study is organization. Sample of this study is 604 observations during 2001-2007. This study uses purposive sampling to collect data from the Indonesian Stock Exchange. This study collects and searches ultimate ownership on chain of ownership structure in manufacturing companies listed in the Indonesian Stock Exchange. This study uses ultimate ownership to identify family ownership or non-family ownership because the reality of ownership structure in public companies in Indonesia is concentrated. This study identifies direct and indirect ownerships on chain of ownership. Based on direct and indirect, this study can identify ultimate ownership whether are family or non-family ownership. This study uses return on assets to proxy firm performance. The return is operating income. To analysis data, this study uses multiple reggresion model. Dependend variable is firm performance and independen variable is family ownership. The results of this study are family ownership negatively affect to firm performance. It indicates that ownership by family reduce firm performance. These results suggest that entrenchment effect is more dominant than alignment effect on the family ownership. The research focus only for manufacturing industry and data is only from 2001-2007. The results of the study will impact for regulation to lead listed companies have to disclosure the ultimate owner because it is a potential agency problem in Indonesia. The results also give information for potential and existing investor to give more pay attention on financial statements because it is potential to mislead on the statements. Keywords : Ultimate Ownership, Family, Firm Performance, Entrenchment Effect